Adverse childhood experiences and perceived body size across the life course: a longitudinal study using data from the Canadian Longitudinal Study on Aging (CLSA) - Jean-Eric Tarride; Laura N Anderson; Lauren Griffith; Andrea Gonzalez; Vanessa De Rubeis (BMJ Public Health)
Background Early life adversity has long-term effects; however, the influence on changes in body size across the life course is not well understood. Objectives of this study were to define trajectories of body size across the life course and to evaluate the association between adverse childhood experiences (ACEs) and perceived life course body size trajectories.Methods A longitudinal study using data from the Canadian Longitudinal Study on Aging (CLSA) was conducted (n=11 830). Adults aged 49–93 were asked to recall eight ACEs and their perceived body size at ages 25, 45, 55, 65 and current using pictograms. Body size trajectories were identified using latent class growth mixture modelling. Multinomial logistic regression was used to estimate ORs and 95% CIs for the association between ACEs and perceived body size trajectories. Effect modification by sex was explored.Results Six distinct life course body size trajectories were identified: consistently low (9.7%), consistently mid-size (24.7%), moderate increase (37.4%), strong increase (14.7%), decline (4.9%) and consistently high (8.6%). High ACE exposure, compared with none, was associated with increased odds of the strong increase (OR: 1.49; 95% CI: 1.21 to 1.83) and consistently high (OR: 1.36; 95% CI: 1.08 to 1.73) body size trajectories, compared with the moderate-increase trajectory. For females, there was a strong association for those who reported 4–8 ACEs with the consistently high trajectory (OR: 1.70; 95% CI: 1.24 to 2.34) but no association for males (OR: 0.99; 95% CI: 0.69 to 1.41).Discussion Distinct patterns of body size throughout the life course exist. ACEs are associated with trajectories that are characterised by obesity incidence in both early and later life.